MAPPING AND INDEX VEGETATION ANALYSES OF MANGROVE IN SAPARUA ISLAND, CENTRAL MOLUCCAS - Harold J. D. Waas; Bisman Nababan (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2010)
2TMapping and index vegetation analyses of mangrove in coastal areas of Saparua Island, Central Moluccas was conducted using Landsat 7/ETM+ satellite data acquired in April to May 2007. The results showed that the distributions of mangrove vegetation were concentrated in the north, south, and west of the region with the area of 218.88 ha (38.26%), 105.12 ha (18.38%), and 248.04 ha (43.36%), respectively. Total area of mangrove vegetation in this island was about 572.04 ha (5.72 kmP2P), or 3.49% of the island area. Vegetation indexes (NDVI) in the north, south, and west of the region were dominated by values of >0.7 (very high density).Keyword: Mangrove, NDVI, Landsat Satellite, Saparua, Central Maluku